6x+12=-3

Simple and best practice solution for 6x+12=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+12=-3 equation:



6x+12=-3
We move all terms to the left:
6x+12-(-3)=0
We add all the numbers together, and all the variables
6x+15=0
We move all terms containing x to the left, all other terms to the right
6x=-15
x=-15/6
x=-2+1/2

See similar equations:

| -5x+9=8x-56 | | -20+2x=16+4x | | -12=-6(w+1) | | x^=7 | | -7q-50+3q=-26 | | 26=10x-(3x+30) | | 2x+2-3x÷4=24 | | (2x+1)+2(2x-3)+15-2x=180 | | 2w+17=6w-51 | | 7x•=49 | | 1/2x+2=3/5x | | 19k-16k-k-1=11 | | 5x+22=3x+28 | | 4x+45=7x-2=6x-16 | | 4x+45=7x-2 | | 8n+5n+4n-(-14)=-20 | | 4x-22=18 | | 5/x=6/2 | | 15+y=22 | | -2y+(-5y)-(-20)=-15 | | -20-2x=16-4x | | w-4.23=9.34 | | 6x^+1=13 | | 56d−2=3 | | 7x^=49 | | 23c+6=8 | | 19t-(-9t)-(-18)=-10 | | 12y+25=–35 | | 0.4x-1.4=3.2x-7.6-0.4x | | (8/3x+3/2=3/2=19/4) | | 3x+x+(x-8)=133 | | 0.4x-1.4=3.2x-7.2-0.4 |

Equations solver categories